“Implementación de un prototipo de Extrusora de plásticos para la carrera de electromecánica de la Universidad Técnica de Cotopaxi”. - Gallo Muela, Alex Mauricio (2022)
The present project consisted in the implementation of a prototype of a plastic extruder for the Electromechanics career of the Technical University of Cotopaxi. The raw material used was low density polyethylene of 0.94 gr/cm3 where it is necessary to reach a temperature of 180 °C for its melting. The design of the extruder machine begins with the construction of a square hopper of galvanized tool for a capacity of 8.27 kg, the worm screw was made of AISI 4140 steel with 50.8 mm in diameter and 650 mm long, for the extruder cylinder was also used AISI 4140 steel with an inner diameter of 64.2 mm and 675 mm long, the mold was made of AISI 1018 steel with the measures of the final product which is the rectangular profile of height and width: 7 cm and length 25 cm, for the cooling system was built a tub of height and width: 15 cm and 35 cm high and finally a support structure manufactured in AISI 1010 square structural steel of 38 mm side and 1.5 mm thick. A control board was implemented for starting the 2 HP electric motor at 220 Vac and for the on/off temperature control using the CH-102 controller, two thermocouples and 5 300 W clamp type resistors allowing its on/off according to a 180 °C reference value. Finally, the extruder operation tests were developed, allowing to obtain a rectangular profile of 7 cm x 7 cm x 25 cm with a mass quantity of 1.15 kg.